Shranjevanje toplote z geosondami in testi za ugotavljanje toplotnih lastnosti zemlje - primer uporabe v Turčiji ter stanje v Sloveniji - Stritih, Uroš (Strojniški vestnik, 2004)
In the paper we present a method of seasonal heat storage with boreholes and thermal response test for determination of ground parameters. Analysis methods for concrete calculations of thermal conductivity as well as error determination are explained. In the continuation measurements made in research of the ground in Turkey and situation in a field of seasonal thermal energy storage in Slovenia are presented.
Keywords: hranjenje toplote; hranjenje podzemno; geosonde; prevodnost toplotna; shranjevanje toplote